Targeting iron metabolism in cancer to induce ferroptosis: a type of programmed cell death - Rhiannon Beadman (2024)
Cancer patients undergo a number of procedures in order to eradicate tumours. Although cancer patients are often highly responsive to initial treatment, acquired resistance can lead to a relapse in disease. Due to increased metabolism to sustain rapid proliferation, cancer cells are vulnerable to the induction of ferroptotic cell death; a form of programmed cells death-dependent on iron and the accumulation of lipid peroxides. Cancers cells are known to evade ferroptosis through the upregulation of the key enzyme glutathione peroxidase IV (GPX4), which therefore provides a potential therapeutic target. This study used ferroptosis inducers: Erastin and RSL3, which inhibit GPX4 indirectly and directly respectively. A novel ferroptosis-inducing iron oxide nanoparticle was also synthesised for this study. This study used a panel of cancer cell lines: breast, colon, lung and three ovarian cancers which modelled different chemotherapy sensitivities. Ferroptosis was characterised by the accumulation of lipid peroxides and changes in GPX4. Ferroptosis was confirmed after the addition of a lipid peroxide scavenger, which rescued against Erastin and RSL3 induced ferroptotic cell death. Autophagy induction was also investigated to determine the role autophagy regulators may play in ferroptotic induction. Overall, cancer cells were more susceptible to RSL3-induced ferroptotic cell death. Autophagy was induced and inhibited through the activation and inhibition of AMPK, respectively, resulting in changes in ferroptotic induction in the cancer cells, which requires further investigation. Furthermore, the ferroptosis-inducing iron oxide nanoparticles induced cancer cell death, which was characteristic of ferroptosis. Therefore, ferroptosis could be exploited as a therapeutic target for cancer nanotherapy.